Analysis of the causes of low birth weight infants in terms of nutritional status and maternal health history - Utami, Sri; Susilaningrum, Rekawati (Jurnal Ners, 2022)
Introduction: The incidence of low-birth-weight infants is still high and requires serious attention to prevent infant mortality. This study aimed to analyze the causes of low-birth-weight infants' nutritional status and maternal health history. Methods: This cross-sectional study was conducted in May to July 2021 at two hospitals in Surabaya. The study involved 498 mothers who had newborns within three years from 2019 and were recruited using simple random sampling. The inferential test was conducted using logistics regression with a significance level of 0.05. Results: According to the adjusted model, variables that were significantly associated with the incidence of low-birthweight infants were the husband's job as private worker (OR=0.021; 95% CI = 0.023-0.123), child number as one (OR=0.214; 95% CI = 0.114-3.428), parity as prime (OR=0.749; 95% CI = 0.197-3.652) and history of low-birth-weight infants in previous births (OR=0.015; 95% CI = 0.004-0.006). Conclusions: Individual and family factors remand an essential variable in low-birth-weight prevalence. Nurses are responsible for providing socialization to mothers and fathers who are having and planning to have children. Cultural factors in the family and community where the mother lives also need to be carried out in further research.